Dorypteryx longipennis Smithers (Psocoptera Psyllipsocidae) new species for Italy (Bollettino di zoologia agraria e bachicoltura, 2024)
Dorypteryx longipennis Smithers (Psocoptera Psyllipsocidae) was recorded for the first time in Italy. The species was found in a private house, recently restructured.
Keywords: Dorypteryx longipennis; Psocoptera; domestic situation; Italy